Pemberdayaan Petani Jamur melalui Desain Rumah Jamur yang Inklusif - Wiyatiningsih; Winta Tridhatu Satwikasanti; Stefani Natalia Sabatini (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2022)
As a part of the Agrilab Inclusive farming programme, Pusat Rehabilitasi Yakum collaborated with the Institute for Research and Community Service, Universitas Kristen Duta Wacana in assisting the design and development of the inclusive mushroom house which is owned by the farmers under the Yakkum Difable Person Organisation in Cangkep Lor, Purworejo. The design process was conducted by utilizing the participatory design method. The enquiry phase included the determination of the most demanding capabilities in the mushroom-farming context. The problems were mainly found in accessibility. For instance, the visually impaired farmer required non-visual stimulus. In addition, motion or space adjustment was also needed by wheelchair-using farmers. The action-research method in this programme intended to develop a mushroom house with adequate, accessible pathways and an automatic misting system that eased the difficulties faced by farmers with disabilities. The results showed that the solutions increased the productivity of mushroom farming, promoted a positive experience in mushroom cultivation both for farmers with and without disabilities. The participation of mushroom farmers during the design process was the key to the sustainable mushroom house. This approach allowed the mushroom farmers to understand the inclusive design principles and to adjust the design to meet their capabilities and local sources. Therefore, they could accommodate maintenance and implement future development independently.